Hybrid microstructure-based stretchable biosensors for multi-physiological signal sensing - Fei Han; Hanfei Li; Laixin Huang; Xiaomeng Zhou; Rui Su; Huan Yu; Qiong Tian; Hang Zhao; Qingsong Li; Jing Sun; Mei Yu; Xinping Deng; et al. (eScience)
Wearable biosensors provide continuous, real-time physiological monitoring of biochemical markers in biofluids such as sweat, tears, saliva, and interstitial fluid. However, achieving high stretchability and stable biochemical signal monitoring remains challenging. Here, we propose a hybrid microstructure (HMS) strategy to fabricate highly stretchable multifunctional biosensors capable of detecting sweat electrolyte concentrations, pH levels, and surface electromyography (EMG) signals. By integrating a HMS, stable conductivity under large strains is ensured. Stretching tests up to 5000 cycles demonstrated the electrodes’ stretchable stability and reliability. The high-performance electrodes were used for EMG monitoring on human skin. Additionally, active materials were coated onto the stretchable electrodes to create multifunctional sweat sensors capable of monitoring pH as well as calcium, sodium, and potassium ions (Ca2+, Na+, K+). The electrodes reliably maintained their functionality under 60​% strain, providing new insights into the fabrication of stable, highly stretchable biosensors.